Process simulation for sewer systems by splitting &ndash a case study. (2nd February 2010) - Steinebach, G.; Rentrop, P.; Paffrath, M.; Rosen, R.; , S. Seidl
Process simulation tools for sewer systems are built-up by modules for the simulation of flow, transport and chemical or biological reactions. Moreover, the coupling of the models for a single channel to a network is important. In this paper a splitting approach is presented for the suitable numerical treatment of the governing equations. The flow simulation is based on the one-dimensional Saint-Venant equations. These are combined with advection-diffusion-reaction equations for the transport of substances and their chemical or biological reactions. The Saint-Venant equations are splitted into quasi-linear and non-linear components which are semi-discretised in space separately. This approach is adapted to the equations for channels or rivers with strongly varying bottom elevation or cross sections and partial dry channels. The advection-diffusion-reaction equations are treated by an appropriate discretisation of the different parts. WENO-schemes are proposed for the space-discretisation of the advection terms. Numerical results of a case-study with eight chemical reactions are presented.